Intravitreal injection of bevacizumab for choroidal neovascularisation associated with pathological myopia. Issue 2 (16th August 2006) - Sakaguchi, H; Ikuno, Y; Gomi, F; Kamei, M; Sawa, M; Tsujikawa, M; Oshima, Y; Kusaka, S; Tano, Y
Abstract : Aim: To assess the efficacy and safety of an intravitreal injection of bevacizumab (Avastin®) for myopic choroidal neovascularisation (mCNV). Methods: Intravitreal bevacizumab (1 mg) was injected into eight eyes of eight patients with mCNV in this non-randomised, interventional case series. The best-corrected visual acuity (BCVA) was measured and the optical coherence tomography (OCT) and fluorescein angiography findings were examined before and after treatment. The minimum follow-up time was 3 months. Results: The mean BCVA was 0.26 before treatment and 0.51 at the last visit (p = 0.009). The BCVA improved to two or more lines in six eyes (75%) and remained the same in two eyes (25%). Leakage from the mCNV on fluorescein angiography decreased in seven eyes (87.5%). The choroidal neovascularisation area on fluorescein angiography (p = 0.049) and the foveal thickness on OCT images decreased significantly (p = 0.027) after the treatment. No major complications developed. Conclusion: Intravitreal injection of bevacizumab seems to be an effective and safe treatment for mCNV.